Analysis of Regional Financial Capacity: Case Study of 62 Local Governments in Indonesia - Kumba Digdowiseiso; Muhammad Wahyu Saputra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The ability of local government to finance their administration is one of the main characteristics of regional financial independence. Unfortunately, there are still many regions that depend on the intergovernmental fiscal transfers from the central government, instead of optimizing their own regional revenues, even though regional autonomy and fiscal decentralization in Indonesia, which are aimed at making regions become independent, have been running for two decades since 2001. Regional financial capacity is also one of the criteria that determines the success of underdeveloped areas. This study maps the financial capabilities of underdeveloped regions by using descriptive research method. The data sources from the 2020 regional revenue and expenditure budget in 62 underdeveloped regions according to Presidential Regulation Number 63 of 2020. We utilize the financial capability index, analysis of the pattern of relations between the central and local governments, as well as quadrant analysis. The results of the three analyzes showed that most of the underdeveloped regions are still not financially independent because they still depend on central government assistance.